Theories of economic growth and stagnation, with particular reference to China, 1840-1940 - WANG, N.T. (PSL Quarterly Review, 2014)
The paper provides a brief survey of certain significant contributions to the theory of economic growth and stagnation the further the study of a century of apparent stagnation in China. Two alternative approaches are suggested, the first of which emphasizes new theories in order to direct historical research to hitherto neglected horizons. On the other hand, the second approach emphasizes those theories that are judged especially relevant to the Chinese case. The author contends that the nature of theoretical development in economics, as well as the state of the historical data, require a compromise between these two alternatives in order to best serve the ultimate goal of aiding the development of new theories of growth in general and a theory of Chinese stagnation in particular. JEL: F43, N15, O40, O53